2018
DOI: 10.2139/ssrn.3244929
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Exacerbations and Mortality Among Regular Inhaled Therapies for Patients with Stable Chronic Obstructive Pulmonary Disease: Systematic Review and Bayesian Network Meta-Analysis

Abstract: Background Although exacerbation and mortality are the most important clinical outcomes of stable chronic obstructive pulmonary disease (COPD), the drug classes that are the most efficacious in reducing exacerbation and mortality among all possible inhaled drugs have not been determined. Methods and findings We performed a systematic review (SR) and Bayesian network meta-analysis (NMA). We searched Medline, EMBASE, the Cochrane Central Register of Controlled Trials, ClinicalTrials.gov, the European Union Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…This finding was consistently observed in the on-treatment analyses, the analyses that included offtreatment data, and in sensitivity tipping point analyses. These data extend previous studies that suggested a reduction in mortality using ICS-containing medications in patients with COPD (5,6,8,13,14). We confirm a survival benefit to ICScontaining therapy in a predefined, prospective analysis.…”
Section: Discussionsupporting
confidence: 90%
“…This finding was consistently observed in the on-treatment analyses, the analyses that included offtreatment data, and in sensitivity tipping point analyses. These data extend previous studies that suggested a reduction in mortality using ICS-containing medications in patients with COPD (5,6,8,13,14). We confirm a survival benefit to ICScontaining therapy in a predefined, prospective analysis.…”
Section: Discussionsupporting
confidence: 90%
“…Recent large RCTs [9, 12-17] and meta-analyses [18, 35-38] have shown a superior impact of ICSs/LAMAs/LABAs in improving lung function, reducing acute exacerbation, and increasing symptoms compared with LAMAs/LABAs or ICSs/LABAs, without an increase in the incidence of adverse events. Although experts expect each ICS/LAMA/LABA to yield similar benefits and adverse events, the supporting scientific evidence is not available.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…ICSs/LAMAs/LABAs had significant benefits for the reduction of acute exacerbations [9, 12-15], symptoms [15, 16], and rescue medication use [17], and the improvement of lung function [13, 15, 16] compared with ICSs/LABAs or LAMAs/LABAs in randomized controlled trials (RCTs). Furthermore, we previously showed that triple therapy reduced all-cause mortality compared with other dual or single treatments [18]. Currently, ICSs/LAMAs/LABAs are recommended for some patients with persistent breathlessness or who experienced exacerbations, despite the dual therapies [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, LAMA/LABA combination therapy has been introduced as a more potent treatment than LAMA or LABA alone. Studies and meta-analyses have shown that such combination therapy has a greater effect than monotherapy on lung function, symptoms, quality of life, and acute exacerbations [6][7][8][9][10][11][12][13][14]. In addition, LAMA/LABA combination therapy is associated with less frequent moderate to severe exacerbations than inhaled corticosteroid (ICS)/ LABA combination [8,9,15], although a large trial contradicted these results [16].…”
mentioning
confidence: 99%